Borneo children in an international digital playground: intercultural issues and idiosyncrasies - Fitri Suraya, Mohamad; Alvin Wee, Yeo; Norazila, Abdul Aziz; Rethinasamy, Soubakeavathi (Centre for Academic Information Services, UNIMAS, 2010)
It is often argued that there is a great tendency for communities to be deprived of the benefits that ICT offers particularly due to geographical locations, socioeconomic status, gender and age. This paper describes an initiative to provide greater opportunities to the children of a remote rural community in Bario on the island of Borneo which had been previously equipped with basic ICT facilities. Twenty children, aged between seven to fifteen years, were invited to participate in an international digital playground called the Pangaea programme. The programme is designed to enable children to develop friendships and intercultural awareness with other children from Japan, South Korea, Kenya, and Austria. The paper highlights the initial perception and views of the Bario children during the early stage of the Pangaea programme.